Welding Technique Training and Neon Box Advertising Board for Youth Work Groups in Areas Affected by Earthquake Disasters - Arwizet Karudin; Ambiyar Ambiyar; Bulkia Rahim; Remon Lapisa (Universitas Negeri Padang, 2019)
Abstract: Cubadak Air and Sikapak Barat villages are two villages from many villages affected by the earthquake that hit West Sumatra in 2009. The impact is still felt today. More than eighty percent of the houses and economic facilities of the people in this area were destroyed, so there was a lot of unemployment in this village. The purpose of this activity was to train groups of out of school youth in Cubadak Air and Sikapak Barat villages about welding techniques and the manufacture of neon box advertising boards. The method used in this activity is the provision of theories about the science of materials, welding, workshop management, welding practice techniques, and the manufacture of billboards. The results of this activity were the completion of the signboard of the Al-Abrar Great Mosque and the